Networking technology and implementation method based on 5G slice private line - Yan ZHANG (Dianxin kexue)
With the progressive application of 5G technology in 2B user network, the integration of fixed and mobile collaborative networking and DICT technology is the trend of future development.The establishment of fixed line from 5G network wireless access to 2B user site or cloud system, was analyzed the STN line, OTN line of fixed network, and the 5G network slice defined by 3GPP were used to study and compare the networking characteristics of 5G-STN, 5G-STN into cloud and 5G-OTN of 5G slice line, and the end-to-end specific network capabilities.The fixed-mobile collaborative networking scheme was tested on the operator's network to consolidate and verify 5G slicing private line networking technology, drive the implementation of 5G slicing private line networking technology, and accelerate the integration of “5G+” and the real economy.